Jean-Luc Nancy og kristendommens selvafvikling - Albinus, Lars (Religionsvidenskabeligt Tidsskrift, 2017)
The aim of this article is, on the one hand, to present Jean-Luc Nancy’s thought about the deconstruction of Christianity and, on the other, to suggest its possible significance for the general study of religion. According to Nancy, who belongs to a line of thinkers spanning from Nietzsche through Heidegger to Derrida, Christianity initiated the loss of meaning (sens) which permeates the contemporary (notion of) the world. Yet, at the same time, Christianity opens an alterity in the midst of the world owing to the pre-Christian roots of Christ as a redeemer of this world. In a wider perspective, Nancy locates the emergence of religion in a first distinction (as between light and shade) from which the order of the world evolves. In modernity, however, this distinction, or ‘the divine’ as such, only greets us in passing, reflecting the relations between all things of the world which thus salute one another in mutual exposition, that is, in their ex-istence.Hensigten med denne artikel er på den ene side at præsentere Jean-Luc Nancys tanker omkring kristendommens dekonstruktion og på den anden side at antyde hans mulige betydning for en religionsvidenskabelig faghorisont. For Nancy, der specielt står i arv til tænkere som Nietzsche, Heidegger og Derrida, danner kristendommen baggrund for det betydningstab, der kendetegner en moderne (opfattelse af) verden. På samme tid vidner kristendommen imidlertid om den før-kristne Kristus, der som en forløser af denne verden har åbnet en ‘andethed’ midt i den. I et videre perspektiv ser Nancy al religions tilblivelse i en første spaltning (som mellem lys og skygge), hvorfra verden kan fremstå som orden. I moderniteten optræder denne spaltning, eller det guddommelige som sådan, alene som en forbipasserende ‘frelse’ (salut) eller ‘hilsen’ (salut), der reflekterer den måde, hvorpå alt i verden hilser hinanden i gensidig eksponering, dvs., eks-istens.